Antimicrobial Peptides: A New Hope in Biomedical and Pharmaceutical Fields - Moretta, Antonio; Scieuzo, Carmen; Petrone, Anna Maria; Salvia, Rosanna; Manniello, Michele Dario; Franco, Antonio; Lucchetti, Donatella; Vassallo, Antonio; Vogel, Heiko; Sgambato, Alessandro; Falabella, Patrizia (Frontiers in Cellular and Infection Microbiology, 2021)
Antibiotics are essential drugs used to treat pathogenic bacteria, but their prolonged use contributes to the development and spread of drug-resistant microorganisms. Antibiotic resistance is a serious challenge and has led to the need for new alternative molecules less prone to bacterial resistance. Antimicrobial peptides (AMPs) have aroused great interest as potential next-generation antibiotics, since they are bioactive small proteins, naturally produced by all living organisms, and representing the first line of defense against fungi, viruses and bacteria. AMPs are commonly classified according to their sources, which are represented by microorganisms, plants and animals, as well as to their secondary structure, their biosynthesis and their mechanism of action. They find application in different fields such as agriculture, food industry and medicine, on which we focused our attention in this review. Particularly, we examined AMP potential applicability in wound healing, skin infections and metabolic syndrome, considering their ability to act as potential Angiotensin-Converting Enzyme I and pancreatic lipase inhibitory peptides as well as antioxidant peptides. Moreover, we argued about the pharmacokinetic and pharmacodynamic approaches to develop new antibiotics, the drug development strategies and the formulation approaches which need to be taken into account in developing clinically suitable AMP applications.